Multi-aspect analysis and RSM-based optimization of a novel dual-source electricity and cooling cogeneration system. (15th February 2023) - Azizi, Saeid; Shakibi, Hamid; Shokri, Afshar; Chitsaz, Ata; Yari, Mortaza
Graphical abstract: Fig. Ⅰ. Graphical presentation of the work. Highlights: A novel cogeneration system based on natural gas and geothermal energies was proposed. Response surface methodology was used for the statistical analysis. Multi-criteria analyses and multi-objective grey wolf optimization were applied. Optimal exergy efficiency and product cost were obtained 45.2% and 3.82 $/GJ, respectively. Abstract: In light of the movement toward sustainable development and environmental protection, this work proposes a novel cogeneration system using geothermal and natural gas dual-sources. The proposed plant is a combination of the gas turbine cycle with thermophysical recuperation, double-flash geothermal cycle, parallel dual-pressure Kalina cycle, and single-effect absorption cooling cycle for simultaneous power and cooling production. For performance investigation, energy, exergy, exergoeconomic, and economic analyses were performed. To have the optimum operating conditions of the system, a coupled model of the response surface methodology, multi-objective grey wolf optimization algorithm, and four different decision-making methods were suggested. The findings revealed that the combustion chamber has the highest contribution to total exergy destruction by 3885 kW. Based on the economic analysis, considering cooling selling cost of 0.07 $/kWh and fuel purchase cost of 3 $/GJ, increasing electricity cost to 0.15 $/kWh results in total revenue of 76.6 $M with a payback period of 0.66 years. This means that the system with mentioned prices is attractive for investment since it's profitable after some years of operation. Also, according to the optimization results, in the first optimization scenario, the optimum exergy efficiency and sum unit cost of products are determined to be 45.2 % and 3.82 $/GJ.